Carbon-silicon composite porous material as well as preparation method and application thereof

By mixing coal gasification slag with activator and water for carbonization and calcining, combined with acid water washing and drying, a carbon-silicon composite porous material with a high specific surface area was prepared, which solved the problem of coal gasification slag treatment and low specific surface area of ​​porous materials, and achieved efficient carbon dioxide adsorption effect.

CN119608108APending Publication Date: 2025-03-14INST OF COAL CHEM CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856062.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, most coal gasification slags are stacked and landfilled, resulting in ecological environment impact and waste of resources, and the specific surface area of ​​the prepared porous materials is relatively low.

Method used

By mixing coal gasification slag, activator and water for carbonization and calcining, a preliminary carbon-silicon porous material is obtained, and washed and dried by mixing water with acid and water to prepare a carbon-silicon composite porous material with a high specific surface area.

Benefits of technology

It has achieved a high specific surface area of ​​carbon-silicon composite porous materials, a good pore structure, and can be used as a good adsorption carrier. It is widely used for adsorption of carbon dioxide, and has the potential for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608108A_ABST
    Figure CN119608108A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coal-based solid waste recycling, and particularly relates to a carbon-silicon composite porous material and a preparation method and application thereof. The carbon-silicon composite porous material provided by the invention is high in specific surface area and good in pore structure, can be used as an adsorption carrier, and is high in adsorption capacity and good in adsorption effect. According to the invention, the cheap coal gasification slag is used as a raw material, the carbon-silicon composite porous material with a high specific surface area is obtained by combining carbon and mineral substances in the coal gasification slag through a dynamic cavitation chelation method and synergistic pore building, rich mineral substances and residual carbon in the coal gasification slag are utilized to a higher degree, and all-component comprehensive utilization of the coal gasification slag is realized. In addition, the carbon-silicon proportion is effectively regulated and controlled through the activating agent, and directional regulation and control of the pore structure are achieved. The carbon-silicon composite porous material provided by the invention is high in specific surface area, can be used as a good adsorption carrier, is widely applied to the field of adsorption, such as removal of carbon dioxide in flue gas, and has the potential of large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of coal-based solid waste resource utilization, and specifically relates to a carbon-silicon composite porous material and a preparation method and application thereof. Background Art

[0002] Coal gasification slag is a solid waste produced by the coal gasification process, which is mainly composed of residual carbon and mineral particles. The carbon content of coal gasification slag is high, generally between 30% and 60%. This is because of the incomplete conversion of carbon and the transition of carbon to slag during the coal gasification process. Moreover, under the action of high temperature and multiple gases, the carbon undergoes processes such as gasification and activation, and has completely different properties from the carbon in the raw coal. The carbon crystal structure of the residual carbon in the coal gasification slag is more ordered, and the specific surface area and pore volume are much larger than the carbon in the raw coal. The minerals in the coal gasification slag are mainly aluminosilicates, mostly in the form of amorphous glass, quartz and mullite, and contain a small amount of FeO. x , TiO2 and CaO, as well as trace amounts of heavy metal impurities (such as As, Hg, Se, Pb, Cd and Cr). In addition, the content of mineral particles in coal gasification slag is higher than that of residual carbon particles, and the content of mineral particles is generally above 50%, and some are as high as above 80%.

[0003] At present, coal gasification slag is mostly disposed of by stacking and landfilling, which not only affects the ecological environment, but also causes a waste of resources. A small amount of coal gasification slag has been prepared into porous materials. These porous materials can be roughly divided into two categories, one is the multi-level porous material prepared using the residual carbon in the coal gasification slag, and the other is the molecular sieve material prepared by the hydrothermal method using the silicon source in the coal gasification slag. However, the specific surface area of ​​these porous materials is relatively low. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon-silicon composite porous material and a preparation method and application thereof. The carbon-silicon composite porous material provided by the present invention has a high specific surface area.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a carbon-silicon composite porous material, the chemical composition of which includes carbon-silicon and the specific surface area of ​​which is 700 to 1000 m 2 / g.

[0007] Preferably, the carbon-silicon composite porous material has a pore size of 2-4 nm and a pore volume of 0.46-0.65 cm 3 / g.

[0008] Preferably, the particle size of the carbon-silicon composite porous material is 10 to 50 μm.

[0009] The present invention also provides a method for preparing the carbon-silicon composite porous material described in the above scheme, comprising the following steps:

[0010] (1) mixing coal gasification slag, an activator and water, carbonizing and then calcining to obtain a preliminary carbon-silicon porous material;

[0011] (2) The preliminary carbon-silicon porous material, acid and water are mixed, and then washed and dried in sequence to obtain the carbon-silicon composite porous material.

[0012] Preferably, the activator is a potassium compound; the potassium compound includes one or more of KOH, C6H5K3O7 and KHCO3.

[0013] Preferably, the acid is an inorganic acid; the inorganic acid includes one or more of citric acid and hydrochloric acid.

[0014] Preferably, the temperature at which the preliminary carbon-silicon porous material, acid and water are mixed is 30-60°C.

[0015] Preferably, the carbonization is carried out under heating conditions; the initial temperature of the heating is room temperature, and the end temperature is the calcination temperature; the carbonization is carried out in a protective atmosphere.

[0016] Preferably, the calcination temperature is 700-900°C, and the calcination time is 50-80 min; the calcination is carried out under the condition of alternating introduction of N2 and CO2.

[0017] The present invention also provides the use of the carbon-silicon composite porous material described in the above scheme or the carbon-silicon composite porous material obtained by the preparation method described in the above scheme in carbon dioxide adsorption.

[0018] The present invention provides a carbon-silicon composite porous material. The carbon-silicon composite porous material provided by the present invention has a high specific surface area of ​​700 to 1000 m 2 / g, has good pore structure, can be used as an adsorption carrier, has large adsorption capacity and good adsorption effect.

[0019] The present invention also provides a method for preparing the carbon-silicon composite porous material described in the above scheme. The present invention uses cheap coal gasification slag as raw material, and through the dynamic cavitation chelation method (dynamic cavitation to prepare primary carbon-silicon porous materials, chelation cavitation to prepare carbon-silicon composite porous materials), combines carbon and minerals in the coal gasification slag, and synergistically builds pores to obtain a carbon-silicon composite porous material with a high specific surface area, which utilizes the rich minerals and residual carbon in the coal gasification slag to a higher degree, and realizes the comprehensive utilization of all components of the coal gasification slag. Moreover, the present invention effectively controls the carbon-silicon ratio through an activator to achieve directional regulation of the pore structure.

[0020] The present invention also provides the use of the carbon-silicon composite porous material described in the above scheme or the carbon-silicon composite porous material obtained by the preparation method described in the above scheme in carbon dioxide adsorption. The carbon-silicon composite porous material provided by the present invention has a high specific surface area and can be used as a good adsorption carrier and is widely used in the adsorption field, such as the removal of carbon dioxide in flue gas, and has the potential for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a process flow chart for preparing the carbon-silicon composite porous material of the present invention;

[0023] Figure 2 The nitrogen adsorption-desorption curve and pore size distribution diagram of the carbon-silicon composite porous material prepared in Example 3;

[0024] Figure 3 The adsorption selectivity of the carbon-silicon composite porous material prepared in Examples 1 to 9 for CO2 / N2. DETAILED DESCRIPTION

[0025] The present invention provides a carbon-silicon composite porous material, the chemical composition of which includes carbon-silicon and the specific surface area of ​​which is 700 to 1000 m 2 / g.

[0026] In the present invention, the pore size of the carbon-silicon composite porous material is preferably 2-4 nm, and the pore volume is preferably 0.46-0.65 cm 3 / g.

[0027] In the present invention, the particle size of the carbon-silicon composite porous material is preferably 10 to 50 μm, specifically 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm.

[0028] The present invention also provides a method for preparing the carbon-silicon composite porous material described in the above scheme, comprising the following steps:

[0029] (1) mixing coal gasification slag, an activator and water, carbonizing and then calcining to obtain a preliminary carbon-silicon porous material;

[0030] (2) The preliminary carbon-silicon porous material, acid and water are mixed, and then washed and dried in sequence to obtain the carbon-silicon composite porous material.

[0031] The present invention mixes coal gasification slag, an activator and water (referred to as the first mixing) for carbonization and then calcination to obtain a preliminary carbon-silicon porous material. In the present invention, the activator is preferably a potassium compound; the potassium compound preferably includes one or more of KOH, C6H5K3O7 and KHCO3; when the activator is KOH, C6H5K3O7 and KHCO3, the mass ratio of KOH to C6H5K3O7 is preferably 2:0.5-1, specifically 2:0.5, 2:0.6, 2:0.7, 2:0.8, 2:0.9 or 2:1, and the mass ratio of KOH to KHCO3 is preferably 2:0.5-1, specifically 2:0.5, 2:0.6, 2:0.7, 2:0.8, 2:0.9 or 2:1.

[0032] The activator used in the present invention has a unique pore-forming gain effect: first, the present invention uses weakly alkaline C6H5K3O7 and KHCO3 in combination with KOH to activate and form pores, which can reduce the corrosiveness of KOH, thereby greatly reducing the corrosiveness to the equipment; second, the unique effect of C6H5K3O7 in the present invention is that C6H5K3O7, as an organic salt, has strong volatility at high temperatures, so the K salt decomposes and embeds with other K substances (including metal K) between the layers of microcrystals on the inner wall of the carbon pores of the coal gasification slag, stretching the aromatic layers to cause them to twist or deform and expand, thereby playing a role. To achieve pore-forming effect; in addition, C6H5K3O7 also acts as a carbon source, supplementing the carbon source in the gasification slag through carbonization activation at high temperature, realizing the regulation of the carbon-silicon ratio in the gasification slag, thereby further realizing the regulation of the pore structure of the gasification slag; finally, the unique role of KHCO3 in the activator of the present invention is that it decomposes into K2CO3, CO2 and H2O during calcination activation, among which K2CO3 plays an activation role similar to KOH, while CO2 and H2O, as common oxidizing gases, provide a certain reaction atmosphere for activation, thereby further promoting the pore formation of the gasification slag. In summary, the mixed activation system of KOH, C6H5K3O7 and KHCO3 complements each other and has a unique gain pore-forming effect.

[0033] In the present invention, the mass ratio of the activator to the coal gasification slag is preferably 0.5 to 2:1, specifically 0.5:1, 0.7:1, 0.9:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1 or 2:1.

[0034] In the present invention, the water is preferably deionized water.

[0035] In the present invention, the first mixing is preferably: mixing coal gasification slag and part of water (referred to as mixing A) to obtain solution A, mixing the activator and the remaining part of water (referred to as mixing B) to obtain solution B; adding the solution B dropwise (referred to as first dropping) to the solution A and then stirring (referred to as stirring A) to obtain a mixed slurry. In the present invention, the activator solution is added dropwise to the coal gasification slag aqueous solution, which can prevent the activator solution from being too high in concentration and causing insufficient impregnation, thereby allowing the activator to fully contact with the coal gasification slag and achieve a better impregnation effect.

[0036] In the present invention, the mass ratio of the partial water to the coal gasification slag is preferably 2-4:1, specifically 2:1, 2.2:1, 2.5:1, 2.7:1, 3:1, 3.2:1, 3.5:1, 3.7:1 or 4:1.

[0037] In the present invention, the mixing A is preferably carried out by stirring; the mixing A is preferably carried out in a water bath; the temperature of the mixing A is preferably 40 to 60°C, specifically 50°C.

[0038] In the present invention, the mass ratio of the remaining water to the activator is preferably 3 to 5:1, specifically 3:1, 3.2:1, 3.5:1, 3.7:1, 4:1, 4.2:1, 4.5:1, 4.8:1 or 5:1.

[0039] In the present invention, the mixing B is preferably performed by stirring.

[0040] In the present invention, the first dripping is preferably drop by drop; the time of the first dripping is preferably 4 to 6 hours, specifically 5 hours; the dripping rate of the first dripping is preferably 0.05 to 0.4 g / min, specifically 0.05 g / min, 0.1 g / min, 0.15 g / min, 0.2 g / min, 0.25 g / min, 0.3 g / min, 0.35 g / min or 0.4 g / min; the equipment for the first dripping is preferably a dropper.

[0041] In the present invention, the stirring temperature of the stirring A is preferably 30-70° C., specifically 40° C., 50° C. or 60° C.; the stirring A is preferably stopped when the system is stirred into a slurry state.

[0042] In the present invention, the carbonization is preferably carried out under heating conditions; the initial temperature of the heating is preferably room temperature, and the end temperature is preferably calcination temperature; the carbonization is preferably carried out in a protective atmosphere; the protective atmosphere is preferably nitrogen; and the carbonization equipment is preferably a high-temperature furnace.

[0043] In the present invention, the calcination temperature is preferably 700-900°C, specifically 700°C, 750°C, 800°C, 850°C or 900°C, the heat preservation calcination time is preferably 50-80min, specifically 50min, 60min, 70min or 80min; the calcination is preferably carried out under the condition of alternating introduction of N2 and CO2; the single introduction time of CO2 is preferably 20-30min, specifically 20min, 24min, 27min or 30min; the single introduction time of N2 is preferably 30-50min, specifically 30min, 35min, 40min, 45min or 50min; the number of times of alternating introduction of N2 and CO2 (introducing 1 time of N2 and 1 time of CO2 is counted as 1 time) is preferably 3-5 times, specifically 4 times; the calcination equipment is preferably a high-temperature furnace. The present invention uses dynamic calcination to carry out the activation process in different atmospheres in stages, thereby effectively avoiding uneven pore size distribution and the generation of macropores, and significantly improving the specific surface area and porosity of the material.

[0044] The preparation method provided by the present invention has a unique activation gain effect: the mixed material dried to a muddy state contains a certain amount of moisture, and during calcination activation, water vapor and carbon in the coal gasification slag undergo an etching and degassing reaction at high temperature, and the generated hydrogen and carbon monoxide etch and cut the carbon pores from the inside out, thereby achieving the effect of pore formation; in addition, the active metals in the coal gasification slag, such as iron oxide and aluminum oxide, are reduced to metal elements by the generated reducing gas and utilized by secondary cavitation, thereby further promoting the generation of pore structure.

[0045] The present invention uses an air intake method of intermittent ventilation of CO2 and N2 during calcination, which is a method of dynamic atmosphere control. Traditional alkali activation methods usually use constant atmosphere conditions, which makes it difficult to achieve precise control of the pore structure. The present invention intermittently introduces N2 and CO2 to allow the activation process to be carried out in stages in different atmospheres. This dynamic atmosphere control method breaks the traditional activation method. The frequency, duration and activation temperature of gas introduction can be accurately controlled through intermittent ventilation, thereby effectively avoiding uneven pore size distribution and the formation of macropores, significantly improving the specific surface area and porosity of the material, and realizing real-time environmental switching during the activation process, making pore formation more controllable, and being able to selectively generate micropores and mesopores according to demand.

[0046] Secondly, in the alkaline activation reaction (calcination), alkaline activators such as KOH will decompose at high temperature to generate K2O and water vapor with strong activation ability, the latter of which can react with carbon to generate pores (C+H2O→CO+H2). Nitrogen, as an inert gas, will not participate in the oxidation reaction when it is intermittently introduced, and can "dilute" the strong reaction of alkaline activation at certain stages. This intermittent introduction of nitrogen plays the role of a "buffer" in the activation reaction, reducing the destructive oxidation of the carbon structure, avoiding the formation of overly large pores, and keeping the pore size distribution concentrated in the micropore and small mesopore range. This control reduces the risk of structural collapse and fragmentation, thereby increasing the specific surface area and mechanical stability of carbon-silicon composite porous materials.

[0047] Finally, in the alkaline activation reaction, the activator KOH can enter the interior of the carbon material, and the potassium oxide and potassium gas generated after decomposition can further expand the pores through chemical reactions. When N2 and CO2 are introduced intermittently, the pore generation process is more controlled, forming regular micropores and mesoporous structures. The intermittent introduction of nitrogen can reduce the collapse of the pore wall and maintain the structural integrity of the pores; while the introduction of CO2 "digs" out more small pores and micropores at the appropriate stage, increasing the specific surface area of ​​the material.

[0048] After obtaining the preliminary carbon-silicon porous material, the present invention mixes the preliminary carbon-silicon porous material, acid and water (referred to as the second mixing), and then washes and dries in sequence to obtain the carbon-silicon composite porous material. In the present invention, the acid is preferably an inorganic acid; the inorganic acid preferably includes one or more of citric acid and hydrochloric acid; when the acid is citric acid and hydrochloric acid, the mass ratio of citric acid to hydrochloric acid is preferably 5 to 10:1, specifically 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.

[0049] When the present invention performs chelating cavitation activation pore formation, the mixed acid system of citric acid and hydrochloric acid has a unique gain effect: first, citric acid is an organic weak acid, which can react with the metal element reduced in the first activation reaction to perform cavitation pore formation, thereby realizing secondary pore formation; second, citric acid is a commonly used chelating agent, and multiple coordinating atoms in its molecules form a ring-structured complex with metal ions, thereby fixing the metal ions, and therefore can form a complex with the metal ions in the coal gasification slag through chelation, further removing the impurity metal ions in the coal gasification slag, thereby removing the impurities remaining in the pores of the coal gasification slag, and achieving the effect of further pore formation; third, citric acid is a weak acid, and its corrosiveness is greatly reduced compared with the existing acid leaching method, thereby greatly reducing the corrosion to the equipment.

[0050] The present invention uses a mixed acid system of citric acid and hydrochloric acid for secondary cavitation pore formation. Hydrochloric acid has a unique gain effect: the first function is to further remove the metal impurity ions contained in the coal gasification slag and promote pore formation; secondly, the removal of metal ions by citric acid is also closely related to the pH value of the system. The greater the acid effect, the better the removal effect. Therefore, the second function of hydrochloric acid is to provide a suitable acidic environment for citric acid to chelate and remove metal ions.

[0051] In the present invention, the mass ratio of the preliminary carbon-silicon porous material to the acid is preferably 1:4-6, specifically 1:4, 1:4.5, 1:5, 1:5.5 or 1:6.

[0052] In the present invention, the water is preferably deionized water.

[0053] In the present invention, the mass ratio of the preliminary carbon-silicon porous material to water is preferably 1:3-5, specifically 1:3, 1:3.5, 1:4, 1:4.5 or 1:5.

[0054] In the present invention, the temperature of the second mixture is preferably 30-60°C, specifically 40°C or 50°C. The chelating ability of citric acid is greatly affected by temperature. Under suitable temperature conditions, citrate has a strong ability to chelate metal ions, but as the temperature rises, its chelating ability will gradually decrease. Therefore, when using a citric acid + hydrochloric acid mixed acid system for cavitation pore formation, controlling the appropriate temperature is crucial to improving the removal effect of citric acid. Therefore, the present invention effectively increases the specific surface area of ​​the carbon-silicon composite porous material by controlling the appropriate temperature.

[0055] In the present invention, the second mixing is preferably: mixing the preliminary carbon-silicon porous material and water (referred to as mixing D) to obtain a solution D, and dropping the acid into the solution D under stirring in a water bath (referred to as the second dropping).

[0056] In the present invention, the mixing D is preferably carried out by stirring; and the mixing D is preferably carried out in a water bath.

[0057] In the present invention, the second dropping is preferably performed drop by drop; the second dropping is preferably stopped when no bubbles are generated in the system.

[0058] In the present invention, the target pH of the water washing is preferably that the filtrate is neutral.

[0059] In the present invention, the drying temperature is preferably 80-110°C, specifically 80°C, 90°C, 100°C, 105°C or 110°C, and the heat preservation and drying time is preferably 12-24h, specifically 12h, 15h, 18h, 21h or 24h.

[0060] In the present invention, the drying preferably further includes grinding the obtained product.

[0061] The present invention also provides the use of the carbon-silicon composite porous material described in the above scheme or the carbon-silicon composite porous material obtained by the preparation method described in the above scheme in carbon dioxide adsorption.

[0062] The carbon-silicon composite porous material provided by the present invention has a high specific surface area, can be used as a good adsorption carrier, and is widely used in the adsorption field, such as the removal of carbon dioxide in flue gas, and has the potential for large-scale promotion and application.

[0063] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0064] Example 1

[0065] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0066] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0067] Weigh 6 g of coal gasification slag and dissolve it in 12 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 1 g of KOH, 0.5 g of KHCO3 and 0.5 g of C6H5K3O7, mix them evenly and dissolve them in 9 g of water to prepare solution B; then add solution B to solution A through a dropper for 4 hours; continue heating and stirring after adding until it is in a slurry state to obtain a mixed slurry;

[0068] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 700°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 30 minutes, and this is repeated 3 times. After cooling, the mixed slurry is ground to obtain a primary carbon-silicon porous material;

[0069] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0070] 3 g of primary carbon-silicon porous material was weighed and dissolved in 9 mL of deionized water to prepare solution D, and stirred in a water bath at 30°C; 10 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 10 g of water to prepare solution E; then, solution E was added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0071] (3) Activity evaluation

[0072] 0.8 g of the carbon-silicon composite porous material of this embodiment was weighed, and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 10%, and the volume content of N2 was 90%), adsorption temperature T=30°C, flow rate 50 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0073] Example 2

[0074] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0075] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0076] Weigh 6 g of coal gasification slag and dissolve it in 18 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 3 g of KOH, 1.5 g of KHCO3 and 1.5 g of C6H5K3O7, mix them evenly and dissolve them in 24 mL of water to prepare solution B; then add solution B to solution A through a dropper for 5 hours; continue heating and stirring after the addition until it is in a slurry state to obtain a mixed slurry;

[0077] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 800°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 40 minutes, and this is repeated 3 times. After cooling, the mixed slurry is ground to obtain a primary carbon-silicon porous material;

[0078] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0079] 3 g of primary carbon-silicon porous material was weighed and dissolved in 12 mL of deionized water to prepare solution D, and stirred in a water bath at 40°C; 12 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 12 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0080] (3) Activity evaluation

[0081] 1 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 12% and the volume content of N2 was 88%), adsorption temperature T=40°C, flow rate 60 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0082] Example 3

[0083] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0084] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0085] Weigh 6 g of coal gasification slag and dissolve it in 24 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 7 g of KOH, 3.5 g of KHCO3 and 1.5 g of C6H5K3O7, mix them evenly and dissolve them in 60 g of water to prepare solution B; then add solution B to solution A through a dropper for 6 hours; continue heating and stirring after adding until it is in a slurry state to obtain a mixed slurry;

[0086] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 900°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 50 minutes, and this is repeated 3 times. After cooling, the mixed slurry is ground to obtain a primary carbon-silicon porous material;

[0087] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0088] 3 g of primary carbon-silicon porous material was weighed and dissolved in 15 mL of deionized water to prepare solution D, and stirred in a water bath at 50° C.; 14 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 14 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0089] (3) Activity evaluation

[0090] 1.2 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 15% and the volume content of N2 was 85%), adsorption temperature T=50°C, flow rate 70 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0091] Example 4

[0092] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0093] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0094] Weigh 6 g of coal gasification slag and dissolve it in 18 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 1 g of KOH, 0.5 g of KHCO3, and 0.5 g of C6H5K3O7, mix them evenly, and dissolve them in 12 g of water to prepare solution B; then add solution B to solution A through a dropper for 5 hours; continue heating and stirring after adding until it is in a slurry state to obtain a mixed slurry;

[0095] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 800°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 40 minutes, and this is repeated 3 times. After cooling, the mixed slurry is ground to obtain a primary carbon-silicon porous material;

[0096] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0097] 3 g of primary carbon-silicon porous material was weighed and dissolved in 12 mL of deionized water to prepare solution D, and stirred in a water bath at 60° C.; 16 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 16 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0098] (3) Activity evaluation

[0099] 1.5 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 12% and the volume content of N2 was 88%), adsorption temperature T=60°C, flow rate 80 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0100] Example 5

[0101] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0102] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0103] Weigh 6 g of coal gasification slag and dissolve it in 12 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 6 g of KOH, 3.5 g of KHCO3, and 1.5 g of C6H5K3O7, mix them evenly, and dissolve them in 27 g of water to prepare solution B; then add solution B to solution A through a dropper for 4 hours; continue heating and stirring after adding until it is in a slurry state to obtain a mixed slurry;

[0104] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 850°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 30 minutes, and this is repeated 3 times. After cooling, the mixture is ground to obtain a primary carbon-silicon porous material;

[0105] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0106] 5 g of primary carbon-silicon porous material was weighed and dissolved in 15 mL of deionized water to prepare solution D, and stirred in a water bath at 40°C; 18 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 18 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0107] (3) Activity evaluation

[0108] 1.8 g of the carbon-silicon composite porous material of this embodiment was weighed, and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 15%, and the volume content of N2 was 85%), adsorption temperature T=70°C, flow rate 70 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0109] Example 6

[0110] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0111] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0112] Weigh 4 g of coal gasification slag and dissolve it in 10 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 4 g of KOH, 1 g of KHCO3, and 1 g of C6H5K3O7, mix them evenly, and dissolve them in 21 g of water to prepare solution B; then add solution B to solution A through a dropper for 6 hours; after titration, continue to heat and stir until it is in a slurry state to obtain a mixed slurry;

[0113] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 750°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 50 minutes, and this is repeated 3 times. After cooling, the mixed slurry is ground to obtain a primary carbon-silicon porous material;

[0114] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0115] 4 g of primary carbon-silicon porous material was weighed and dissolved in 20 mL of deionized water to prepare solution D, and stirred in a water bath at 50° C.; 20 g of citric acid and 2 g of hydrochloric acid were weighed and mixed evenly and dissolved in 20 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0116] (3) Activity evaluation

[0117] 2 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 12% and the volume content of N2 was 88%), adsorption temperature T=50°C, flow rate 60 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0118] Example 7

[0119] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0120] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0121] Weigh 2g of coal gasification slag and dissolve it in 7mL of deionized water to prepare solution A, and stir it in a water bath at 60℃; weigh 2g of KOH, 1g of KHCO3, and 1g of C6H5K3O7, mix them evenly, and dissolve them in 16g of water to prepare solution B; then add solution B to solution A through a dropper for 5h; continue heating and stirring after adding until it is in a slurry state to obtain a mixed slurry;

[0122] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced for carbonization during the heating stage, and when the temperature rises to 850°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 50 minutes, and this is repeated 3 times. After cooling, the mixture is ground to obtain a primary carbon-silicon porous material;

[0123] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0124] 2 g of primary carbon-silicon porous material was weighed and dissolved in 10 mL of deionized water to prepare solution D, and stirred in a water bath at 30°C; 8 g of citric acid and 1 g of hydrochloric acid were weighed, mixed evenly, and dissolved in 10 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0125] (3) Activity evaluation

[0126] 1.4 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 15%, and the volume content of N2 was 85%), adsorption temperature T=30°C, flow rate 50 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0127] Example 8

[0128] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0129] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0130] Weigh 5 g of coal gasification slag and dissolve it in 15 mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 2.5 g of KOH, 1.25 g of KHCO3, and 1.25 g of C6H5K3O7, mix them evenly, and dissolve them in 25 g of water to prepare solution B; then add solution B to solution A through a dropper for 4 hours; after titration, continue to heat and stir until it is in a slurry state to obtain a mixed slurry;

[0131] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 850°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 40 minutes, and this is repeated 3 times. After cooling, the mixture is ground to obtain a primary carbon-silicon porous material;

[0132] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0133] 3 g of primary carbon-silicon porous material was weighed and dissolved in 12 mL of deionized water to prepare solution D, and stirred in a water bath at 50°C; 15 g of citric acid and 3 g of hydrochloric acid were weighed, mixed evenly, and dissolved in 15 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0134] (3) Activity evaluation

[0135] 1.7 g of the carbon-silicon composite porous material of this embodiment was weighed, and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under argon atmosphere for 2 h, and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 13%, and the volume content of N2 was 87%), adsorption temperature T=40°C, flow rate 60 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0136] Example 9

[0137] The process flow of preparing carbon-silicon composite porous material in this embodiment is as follows Figure 1 As shown;

[0138] (1) Preparation of primary carbon-silicon porous materials by one-step dynamic cavitation method

[0139] Weigh 10g of coal gasification slag and dissolve it in 40mL of deionized water to prepare solution A, and stir it in a water bath at 60°C; weigh 10g of KOH, 5g of KHCO3, and 5g of C6H5K3O7, mix them evenly, and then dissolve them in 100g of water to prepare solution B; then add solution B to solution A through a dropper for 5h; after adding, continue heating and stirring until it is in a slurry state to obtain a mixed slurry;

[0140] The mixed slurry is treated in a high-temperature furnace: N2 is continuously introduced during the heating stage for carbonization, and when the temperature rises to 850°C for calcination, CO2 is switched to calcination for 20 minutes, and then N2 is switched to calcination for 30 minutes, and this is repeated 3 times. After cooling, the mixture is ground to obtain a primary carbon-silicon porous material;

[0141] (2) Preparation of carbon-silicon composite porous materials by two-step chelate cavitation method

[0142] 8 g of primary carbon-silicon porous material was weighed and dissolved in 24 mL of deionized water to prepare solution D, and stirred in a water bath at 40°C; 30 g of citric acid and 6 g of hydrochloric acid were weighed, mixed evenly, and dissolved in 30 g of water to prepare solution E; solution E was then added dropwise to solution D through a dropper until no bubbles were generated; then, the mixed slurry of the two-step cavitation was washed and filtered until neutral, and dried to obtain a carbon-silicon composite porous material.

[0143] (3) Activity evaluation

[0144] 2 g of the carbon-silicon composite porous material of this embodiment was weighed and a CO2 adsorption test was carried out in a fixed bed reactor. Before the reaction, the adsorption carrier was purged at 250°C under an argon atmosphere for 2 h and then switched to a CO2 / N2 mixed gas for adsorption. The adsorption conditions were: simulated flue gas (wherein the volume content of CO2 was 15% and the volume content of N2 was 85%), adsorption temperature T=30°C, flow rate 60 mL / min, and the composition of the outlet gas flow was detected by a mass spectrometer. The results are shown in Table 1.

[0145] Table 1 Carbon-silicon composite porous material structure and CO2 adsorption test results prepared in Examples 1 to 9

[0146] sample <![CDATA[Specific surface area m 2 / g]]> Aperture nm <![CDATA[Pore volume cm 3 / g]]> <![CDATA[CO2 adsorption capacity mmol / g]]> Fine slag original 73.43 3.83 0.13 0.52 Example 1 759.05 3.10 0.55 2.47 Example 2 815.92 2.64 0.52 2.66 Example 3 954.28 2.66 0.58 3.58 Example 4 838.60 2.75 0.46 2.79 Example 5 826.13 2.69 0.56 2.67 Example 6 865.63 2.71 0.54 3.08 Example 7 923.81 2.96 0.65 3.27 Example 8 794.47 3.29 0.63 2.60 Example 9 844.81 2.89 0.58 2.85

[0147] It can be seen from Table 1 that the carbon-silicon composite porous material prepared by the present invention has a high specific surface area, diverse pore diameters, a large pore volume, a large carbon dioxide adsorption capacity, and a good adsorption effect.

[0148] Test Example 1

[0149] The carbon-silicon composite porous material of Example 3 of the present invention was subjected to nitrogen adsorption and desorption and pore size distribution tests. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that under low relative pressure, the adsorption amount increases rapidly, which indicates that the carbon-silicon composite porous material prepared by the present invention has a large number of micropores. At the same time, it can be seen from the pore size part diagram that the specific surface area of ​​the coal gasification slag can be effectively improved by dynamic chelating cavitation activation.

[0150] Test Example 2

[0151] The carbon-silicon composite porous materials of Examples 1 to 9 of the present invention were tested for CO2 / N2 adsorption selectivity. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that compared with the initial coal gasification slag material, its adsorption selectivity for CO2 is greatly improved after dynamic chelation cavitation activation, so the present invention can achieve effective directional regulation of the pore structure.

[0152] It can be seen from the above embodiments that the carbon-silicon composite porous material provided by the present invention has a high specific surface area and a good pore structure, can be used as an adsorption carrier, has a large adsorption capacity and a good adsorption effect.

[0153] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A carbon-silicon composite porous material, characterized in that: The chemical composition includes carbon silicon, and the specific surface area is 700-1000m 2 / g.

2. The carbon-silicon composite porous material according to claim 1, characterized in that: The carbon-silicon composite porous material has a pore size of 2 to 4 nm and a pore volume of 0.46 to 0.65 cm 3 / g.

3. The carbon-silicon composite porous material according to claim 1 or 2, characterized in that: The particle size of the carbon-silicon composite porous material is 10-50 μm.

4. The method for preparing the carbon-silicon composite porous material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing coal gasification slag, an activator and water, carbonizing and then calcining to obtain a preliminary carbon-silicon porous material; (2) The preliminary carbon-silicon porous material, acid and water are mixed, and then washed and dried in sequence to obtain the carbon-silicon composite porous material.

5. The preparation method according to claim 4, characterized in that: The activator is a potassium compound; the potassium compound includes one or more of KOH, C6H5K3O7 and KHCO3.

6. The preparation method according to claim 4, characterized in that: The acid is an inorganic acid; the inorganic acid includes one or more of citric acid and hydrochloric acid.

7. The preparation method according to claim 4 or 5, characterized in that: The temperature of mixing the preliminary carbon silicon porous material, acid and water is 30-60°C.

8. The preparation method according to claim 4, characterized in that: The carbonization is carried out under heating conditions; the initial temperature of the heating is room temperature, and the end temperature is the calcination temperature; the carbonization is carried out in a protective atmosphere.

9. The preparation method according to claim 4 or 8, characterized in that: The calcination temperature is 700-900°C, and the calcination time is 50-80 minutes; the calcination is carried out under the condition of alternately introducing N2 and CO2.

10. Use of the carbon-silicon composite porous material according to any one of claims 1 to 3 or the carbon-silicon composite porous material obtained by the preparation method according to any one of claims 4 to 9 in carbon dioxide adsorption.